Validation and Reliability Testing of the Diabetes Management Self-Efficacy Scale (DMSES) in Indonesia - Hertuida Clara; Hassan, Hafizah Che; Nambiar, Nisha (Sahabat Publikasi Kuu, 2026)
Introduction: Self-efficacy is a key factor influencing diabetes self-management, with higher self-efficacy linked to better adherence to self-care and reduced complications. The Diabetic Management Self-Efficacy Scale (DMSES), a 15-item Likert questionnaire, assesses self-efficacy in diet, exercise, blood glucose monitoring, therapy, and foot care. This study aimed to evaluate the validity and reliability of the Indonesian version of DMSES for use among patients with diabetes mellitus. Methods: This cross-sectional study recruited 30 adults with diabetes mellitus, with 26 participants completing the questionnaire. The study was conducted in three stages: (1) translation, (2) content validation, and (3) validity and reliability testing. Forward–backward translation was applied to ensure linguistic and cultural accuracy. Content validity was assessed by a panel of five experts who rated item relevance, and the content validity index (CVI) was calculated. Item validity was examined by correlating individual item scores with total scores, while internal consistency reliability was evaluated using Cronbach’s alpha. Results: During translation, four items were modified to improve cultural and language clarity. The content validity assessment yielded a CVI of 1.00, indicating excellent agreement among experts. Item analysis demonstrated moderate to strong correlations (r = 0.550–0.867), with all correlation values exceeding the critical r table value (0.388), confirming item validity. The internal consistency reliability test produced a Cronbach’s alpha of 0.934, signifying excellent reliability across all items. Conclusion: The Indonesian version of the DMSES demonstrates strong content validity and high reliability, making it a valid and reliable instrument for measuring self-efficacy in patients with diabetes mellitus. These findings support the use of DMSES in future research and clinical practice in Indonesia to assess and strengthen diabetes self-management behaviors.